Quantitation of the Inhibition Effect of Model Compounds Representing Plant Biomass Degradation Products on Methane Production - Silvie Pekařová; Marie Dvořáčková; Petr Stloukal; Marek Ingr; Jana Šerá; Marek Koutny (BioResources, 2017)
During the steam explosion pretreatment of plant biomass, degradation products are generated, and some of these have inhibitory activity against biogas production. The aim of this study was to investigate and quantify the effect of selected model inhibitory compounds on methane production. The results showed no significant inhibition of methane production by furfural at concentrations below 1 g/L. In addition, the microbial community was able to restore biogas production inhibited by this compound after a certain time. 5 hydroxymethylfurfural was evaluated as a more potent inhibitor, with a significant effect above 0.2 g/L. Both compounds were more effective inhibitors with cellulose as the carbon substrate, probably reflecting higher sensitivity of the cellulolytic step in biogas production. No significant inhibition was observed for the phenolic compounds tested, gallic and tannic acids, at concentrations of up to 2 g/L. Thus, the compounds investigated should not represent a problem for the biogas production involving steam explosion preprocessed plant biomass.